Nursing Care for Chronic Kidney Failure Patients with Fluid Management Intervention at the Dr. Regional General Hospital. Djarart Prawiaranegara Serang - giegies, Elsandi; Haryani, Ani (Al Makki Health Informatics Journal, 2023)
Problems often experienced by Chronic Kidney Failure patients undergoing hemodialysis therapy are related to excess fluid intake in the body. Patients with chronic renal failure who do not comply with fluid intake restrictions will experience fluid accumulation, causing pulmonary edema and left ventricular hypertrophy. The buildup of fluid in the body causes the heart and lungs to function hard, resulting in patients becoming tired and short of breath. while intake that is too low results in dehydration, hypotension, and impaired kidney function. Failed Diseases. Monitoring fluid intake and output in patients has proven to be effective in dealing with excess fluid volume. It is hoped that using non-pharmacological therapy is one method for patients with chronic kidney failure with fluid balance and electrolytes in fluid management interventions. The research results were obtained after fluid management was carried out to reduce fluid and electrolyte balance in patients with chronic renal failure, blood pressure improved, edema was reduced, skin turgor was good, there were no additional breath sounds, patients were able to understand the importance of limiting fluid and sodium intake. , and be able to measure and record food intake and urine output independently.